Análisis jurídico y doctrinario a la violación de requisitos y sus efectos en la unión de hecho por acto notarial en el Ecuador - Villalba Quisirumbay, Rosa Zavina (2015)
The Notary Law is the activity of the notary and the parties in the creation of public documents; due to the variety of purposes and internal aspects that exist in the public instrument. In order for the notary law is necessary to be represented by a person, this is the calling or called "notary" is that legal professional who is dedicated to faith and legal certainty for acts and contracts before they are signed for people interested in perpetuating the negotiations and events that lead in their daily lives. One of the notary attributions in our legislation is to solemnize the statement cohabitants of the existence of the union, who have complied with the requirements set out in Article 222 of the Civil Code. The notary will raise the respective minutes, which duly notarized, certified copy to the parties shall be conferred. The requirements of Article 222 of the Civil Code is that there is: stable and monogamous union of a man and a woman, free marriage with another person, forming a de facto household, for a period of over two years obviously with the new rules on the basis of the provisions of the Constitution bonding can occur between people of the same sex. But what has not changed is the convivenvenci for a certain time; This bonding time between the two people must be justified by persons wishing to obtain such a declaration binding Done. However, to avoid any doubt or legal failure is necessary to establish in law Notary for foreign requirements to justify the de facto union for the time established by law request.